Use of Etle Cameras as a Means of Online Ticketing - Yunita Sukma; Bima, Muhammad Rinaldy; Ilham, Muhammad Azham (Qawanin Jurnal Ilmu Hukum, 2025)
This research aims to determine and analyze the effectiveness of using Etle in reducing traffic violations, particularly in the Makassar Police jurisdiction. This research uses an empirical juridical type of research. The sources of data for this research are results from interviews, observations, books, documents, regulations, and other written materials closely related to the object to be discussed. The results obtained from this research indicate that the Polda Makassar institution, particularly the traffic unit in collaboration with the city government, has fulfilled its role as a complaint center, legal assistance service specifically for traffic, policy studies, traffic legislation, and accident handling. The obstacles faced since the implementation of electronic traffic tickets include: issues related to facilities and infrastructure, the quality and quantity of human resources, and network limitations. The factors influencing the implementation of electronic traffic tickets at the Satlantas Polda Makassar are the readiness of technological infrastructure, public awareness, the availability of human resources, and the commitment of leaders and personnel. The recommendation of this research is that the government and related agencies should synergize more in providing assistance and legal aid, conduct comprehensive legal socialization/education efforts to the public, work firmly with the community in the development and handling of electronic traffic tickets, and remind and raise awareness again about the importance of adhering to legal regulations while driving. Abstrak: Penelitian ini bertujuan untuk mengetahui dan menganalisis Efektivitas Penggunaan Etle mengenai bagaimana dalam mengurangi pelanggaran lalu lintas khususnya di Wilayah Polda Makassar. Penelitian ini menggunakan tipe penelitianyuridis empiris. Adapun sumber data penelitian ini adalah hasil dari wawancara, observasi, buku, dokumen, peraturan perundang- undangan, dan bahan-bahan tertulis lainnya yang berkaitan erat dengan objek yang akan dibahas.Hasil yang diperoleh dari penelitian ini menunjukkan bahwa lembaga Polda Mkassar khususnya satuan lalu lintas yang bekerja sama dengan pemerintah kota telah menjalankan perannya sebagai tempat pengaduhan, pelayanan bantuan hukum khususnya lalu lintas, kajian kebijakan, perundang-undangan tentang lalu lintas, dan penanganan kecelakaan. Kendala-kendala yang dihadapi semenjak berlakunya elektronik tilang antara lain: kendala dalam hal sarana dan prasarana, kualitas dan kuantitas sumber daya manusia, dan keterbatasan jaringan. Faktor-faktor yang mempengaruhi pelakasanaan elektronik tilang di Satlantas Polda Makassar adalah faktor kesiapan infrastruktur teknologi, faktor kesadaran masyarakat, faktor kesediaan sumber daya manusia dan faktor komitmen pemimpin dan personil. Rekomendasi penelitian ini adalah diharapkan hendaknya pemerintah dan pihak-pihak instansi yang terkait lebih bersinergi dalam pendampingan dan pemberian bantuan hukum, upaya sosialisasi/ penyuluhan hukum secara menyeluruh kepada masyarakat, bekerja sama secara tegas dengan masyarakat dalam pembinaan dan penanggulangan elektronik tilang yang terjadi pada lalu lintas, serta menghimbau dan menyadarkan kembali arti pentingnya mematuhi aturan-aturan hukum dalam berkendara.